PENGARUH PROFITABILITAS (ROA), BIAYA OPERASIONAL TERHADAP PENDAPATAN OPERASIONAL (BOPO), FINANCING TO DEPOSIT RATIO (FDR), NON PERFOMING FINANCE (NPF), TERHADAP CAPITAL ADEQUACY RATIO (CAR) (SUATU STUDI PADA BANK UMUM SYARIAH) - Khaerani Pudoli, Salsabila; Khrisna Mahardika, Dewa Putra (EDUTECH CONSULTANT, 2019)
This study aims to analyze whether Profitability (ROA), Operating Expenses on Operating Income (OEOI), Non Performing Finance (NPF) and Financing to Deposit Ratio (FDR) are significantly simultaneous and partial to the Capital Adequacy Ratio (CAR) in Commercial Banks Sharia in the period 2014 - 2017.The population in this study is Islamic banking. The sample is determined based on the purposive sampling method, a total of twelve Islamic banks. The secondary data were taken in the form of bank financial statements starting from 2014 until 2017. The technique of data analysis in this research using data panel regression analysis. CAR as the dependent variable, ROA, BOPO, NPF and FDR as independent variables. Data Processing using Eviews software version 9.5.The results provide evidence that ROA, BOPO, NPF and FDR have a significant simultaneous influence on CAR in sharia commercial banks for the period 2014 - 2017. BOPO and NPF partially have a insignificant negative effect on CAR. ROA and FDR partially has a significant effect on CAR.Based on the results of this study, then if Islamic banking wants to increase capital, then Islamic banking needs to suppress Financing to Deposit Ratio (FDR), increase Return On Asset (ROA), accumulation of retained earnings and conducting an Initial Public Offering (IPO)